The Use off Fuzzy Mamdani to Predict Tilapia Production Based on Freshwater Quality - Muhammad Aqshol Dafa Ramadhan; Muhammad Raulian Deyastra; Fawwaz Fadlurohman; Rahmah Syahidah; Muhammad Radithya Naufal Apriansyah; Devara Ryanta Mulya; Nanda Octavia; Ester Angeline; Muhammad Danang Mukti Dermawan; Bagas Wibisono; Bintan Naktavia; Muhammad Surya Ramadhan; Evita Maharani; Yuliandra Rizky; Yahya Ian Keyvin Sitio; Fira Arista Dewi; Ghinna Zulfia; Putri Ryanda; Rezky Damayanti Nur; Fiqri Nurfadillah (Batrisya Education, 2024)
Fish cultivation is a form of animal husbandry that is widely practiced by Indonesian people, whether cultivation is in ponds, rivers, or the sea, fish cultivation in ponds requires regular maintenance and feeding of fish. Excessive feeding also affects the water quality of the cultivation media which also affects the survival of the fish. One solution is to build a water quality monitoring system. A monitoring system can be created based on Fuzzy logic which makes it easier to control water quality. In this research, the sensors used were temperature, pH, DO, and ammonia. The data will then be processed by Matlab and will display the results on the screen.